Differences in Blood Glucose Levels of NaF Plasma with Blood Stored at Room Temperature - Nining Kurniati; Soleha Pane (Jurnal teknologi Kesehatan Borneo, 2023)
Blood glucose is sugar contained in the blood, derived from carbohydrates in the diet, and stored as glycogen in the liver and skeletal muscles. Blood glucose examinations are widely recommended by paraclinics, which aim to screen or monitor diabetes mellitus. Ideally, blood glucose levels should be checked immediately. This study aims to determine the difference in blood glucose levels in NaF plasma immediately checked with stored blood after 2 and 4 hours of storage at room temperature. This type of research is comparative analysis. The sample is venous blood from as many as 30 respondents, taken by random sampling. The blood glucose level in NaF plasma was immediately examined by the GOD-PAP method, and as a comparison, the blood glucose level in NaF plasma with blood stored for 2 hours and the blood glucose level in NaF plasma with blood stored for 4 hours Blood was put in three different NaF (Sodium Flouride) tubes: immediately examined blood, 2-hour stored blood, and 4-hour stored blood. The results of the study found differences in blood glucose immediately checked with blood stored for 2 hours and 4 hours at room temperature with a value of p > 0.05 (p = 0.001 and 0.002). The conclusion of this study was that significant differences were found between blood glucose levels immediately checked with blood stored for 2 hours and 4 hours at room temperature.